Queer and trans-themed books for young readers: a critical review. Issue 6 (1st November 2016) - Bittner, Robert; Ingrey, Jennifer; Stamper, Christine
ABSTRACT: As research on transgender and gender nonconforming children and youth becomes increasingly prevalent in literary scholarship, educational possibilities arise for teachers of children's and young adult (YA) literature in various classroom settings. This article provides a brief history of literature for children and teens containing queer and trans-positive themes, as well as critical reviews of a selection of more prominent contemporary children's and YA texts. The aim in these reviews is not to offer an exhaustive examination of what is available in trans-positive literature for children and youth, but to consider how these texts, and others, may begin to form a pedagogy of possibility that is rooted in gender equity and social justice.